Áp dụng phương pháp đánh giá - dự báo sạt lở - bồi lấp sông khi khảo sát sông Vu Gia và Thu Bồn (Quảng Nam) - Hoàng, Nguyễn Văn; Huệ, Trần Trọng; Tâm, Lê Thị Minh (Vietnam Journal of Earth Sciences, 2001)
Application of the methods of analysis, prediction of river erosion-deposition and river's bank stability in the observation of Vu Gia and Thu Bon rivers (Quang Nam)